MODERNIZATION AND WOMAN IDENTITY IN POLITICAL COMMUNICATION - Ceren Yegen (Selçuk İletişim)
Means which are made use of by the political communication in terms of propaganda studies are wide ranging. Modernism which attaches different views to many concepts ranging from art to identity sometimes constitutes mainstay of these studies. Modern woman identity is used to call woman electors in political communication studies. For example, social media formation called as CHP Retro opened position of modernization and woman identity within political communication up for discussion by the help of visuals prepared via propaganda actions performed on Twitter before 7th June 2015 Turkey General Elections. Therefore in this study, relevant visuals will be analyzed and position of woman-identity and modernization within political communication will be discussed. Keywords: Political Communication, Modernism, Modernization, Art, Woman, Identity.